Noncommutative 5-dimensional subalgebras of a conformal algebra integrable in R; Russian Physics Journal; Vol. 38, iss. 5 - Shapovalov A. V. Aleksandr Vasilyevich; Shirokov I. V.; Lisitsyn Ya. V.; Firstov V. I. (1995, 1995)
Title screen